2009
DOI: 10.1016/j.electacta.2009.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Growth of porous type anodic oxide films at micro-areas on aluminum exposed by laser irradiation

Abstract: Aluminum covered with pore-sealed anodic oxide films was irradiated with a pulsed Nd-YAG laser to remove the oxide film at micro-areas. The specimen was re-anodized for long periods to examine the growth of porous anodic oxide films at the area where substrate had been exposed by measuring current variations and morphological changes in the oxide during the re-anodizing. The chemical dissolution resistance of the pore-sealed anodic oxide films in an oxalic acid solution was also examined by measuring time-vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Thin porous oxides measuring approximately 1 µm in thickness were also formed in the region between the burned oxides (i.e., except for the burned region). This local thickening of the anodic oxide is typically observed when anodizing under the burning conditions [43,62], and similar structures have also been observed during the selective growth of anodic porous alumina films in micro-sized areas of aluminum substrates exposed by imperfections and laser irradiation [65][66][67]. In addition, it was observed that the burned oxides possessed several cracks measuring a few micrometers in width from the surface and throughout their thickness.…”
Section: Growth Behavior Of the Anodic Porous Alumina Formed By Crocomentioning
confidence: 82%
“…Thin porous oxides measuring approximately 1 µm in thickness were also formed in the region between the burned oxides (i.e., except for the burned region). This local thickening of the anodic oxide is typically observed when anodizing under the burning conditions [43,62], and similar structures have also been observed during the selective growth of anodic porous alumina films in micro-sized areas of aluminum substrates exposed by imperfections and laser irradiation [65][66][67]. In addition, it was observed that the burned oxides possessed several cracks measuring a few micrometers in width from the surface and throughout their thickness.…”
Section: Growth Behavior Of the Anodic Porous Alumina Formed By Crocomentioning
confidence: 82%
“…2c). The applied voltage during electrochemical etching was chosen in reference to previous investigations [8,14], and the voltage is a typical value for electrochemical polishing of aluminum. A platinum plate was used as the counter electrode, and the specimens were set in parallel 15 mm from the counter electrode during electrochemical etching.…”
Section: Electrochemical Etching Through the Anodic Oxide Maskmentioning
confidence: 99%
“…1). After the laser irradiation, subsequently electro-and electro-less plating caused a selective metal and organic compound deposition on the exposed aluminum substrate, and microstructure fabrication such as micro-coils [8][9][10][11], printed circuit boards [12][13][14], plastic injection molds [15], three-dimensional (3D) complicated micromachine components [16,17], 3D micro-actuators [18,19], and electrochemical micro-reactors [20], was successfully achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Porous anodic oxide films of aluminum (anodic porous alumina) have been widely investigated as nanotemplates and resist films with good insulating properties for various micro-and nano-technology applications, such as magnetic recording media [1,2], electronic devices [3], biosensors [4], photonic crystals [5][6][7], microlens arrays [8,9], plasmonic devices [10][11][12], three-dimensional microstructures [13][14][15] and other basic nanodevices [16]. When aluminum is anodized in appropriate acidic electrolytes, porous alumina develops, which exhibits a uniform array of hexagonal cells, each containing a uniform cylindrical nanopore at the center [17][18][19][20][21][22] (lower right in Fig.…”
Section: Introductionmentioning
confidence: 99%